P.(L576P) -KIT mutation in GIST: Favorable prognosis and sensitive to imatinib?. Issue 5 (3rd May 2016) - Noujaim, Jonathan; Gonzalez, David; Thway, Khin; Jones, Robin L.; Judson, Ian
ABSTRACT: Exon 11 KIT mutations are found in a majority of gastrointestinal stromal tumors (GIST) and are usually predictive of response to imatinib, a KIT, PDGFRA and ABL inhibitor. Exon 11 mutations with poor sensitivity to imatinib and poor outcome can be observed on rare occasions, including p.(L576P). In silico and in vitro studies suggested a decreased binding affinity for imatinib in p.(L576P) KIT mutations, thereby offering an explanation for their poor outcome and poor response to standard therapy. These observations were further corroborated with anecdotal case reports of refractoriness or non-durable response to imatinib therapy. However, we describe the favorable response to imatinib and outcome in 5 p.(L576P) -KIT mutant GIST patients treated at a tertiary sarcoma referral center. The sensitivity of p.(L576P) -KIT mutations to imatinib, and the prognostic impact of this mutation need to be further evaluated in a larger cohort. Based on our observations, p.(L576P) mutated GISTs should be treated with standard first line imatinib therapy.